2009
DOI: 10.1016/j.molbiopara.2009.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of green tea catechins on apicomplexan hexose transporters and mammalian orthologues

Abstract: Here we have investigated the inhibitory properties of green tea catechins on the Plasmodium falciparum hexose transporter (PfHT), the Babesia bovis hexose transporter 1 (BboHT1) and the mammalian facilitative glucose transporters, GLUT1 and GLUT5, expressed in Xenopus laevis oocytes. (−)-Epicatechin-gallate (ECG) and (−)-epigallocatechin-gallate (EGCG) inhibited d-glucose transport by GLUT1 and PfHT, and d-fructose transport by GLUT5, with apparent Ki values between 45 and 117 μM. BboHT1 was more potently inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 17 publications
2
29
0
1
Order By: Relevance
“…laevis oocytes. Thus, with the hxt 0 GLUT5 system IC 50 value for fructose uptake inhibition by (−)-epicatechin-gallate (ECG) was comparable to the K i value previously reported 18 . Also the IC 50 for MSNBA inhibition of fructose uptake by hxt 0 GLUT5 is comparable to that determined in human breast carcinoma MCF-7 cells and ~10-fold lower than that determined in GLUT5 proteoliposomes 20 , making the yeast system superior to GLUT5 proteoliposomes and comparable to human cell lines systems in assessing GLUT5 inhibition.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…laevis oocytes. Thus, with the hxt 0 GLUT5 system IC 50 value for fructose uptake inhibition by (−)-epicatechin-gallate (ECG) was comparable to the K i value previously reported 18 . Also the IC 50 for MSNBA inhibition of fructose uptake by hxt 0 GLUT5 is comparable to that determined in human breast carcinoma MCF-7 cells and ~10-fold lower than that determined in GLUT5 proteoliposomes 20 , making the yeast system superior to GLUT5 proteoliposomes and comparable to human cell lines systems in assessing GLUT5 inhibition.…”
Section: Discussionsupporting
confidence: 86%
“…Although there is a slight variation between the mutants, their kinetic parameters are similar to those determined in MCF-7 cells 17, 20 or X . laevis oocytes 18 , indicating that the mutations do not have a major influence on the transport mechanism. Reported K M values for human GLUT5 fructose uptake vary between 6 and 15 mM 3, 17, 40 .
Figure 4Transport kinetics and inhibition of GLUT5 mutants in hxt 0 cells.
…”
Section: Resultsmentioning
confidence: 98%
“…The growth‐inhibiting effect of flavonoids has already been demonstrated for Plasmodium falciparum, belonging to the same phylum as A. bombi (i.e., Apicomplexa; Slavic et al. ). Although the presence of secondary metabolites is a very strong hypothesis for explaining the lower prevalence of a subset of parasite species detected in Bombus pascuorum population from invaded sites, additional experimental assays (e.g., test on the biological activities of the secondary metabolites) are needed to fully validate this hypothesis and to understand the associated mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the multidirectional biological activity of I. glandulifera (especially antimicrobial properties due to flavonoids occurrence in pollen) coupled with the active foraging of bumble bee workers on the invasive plant could explain the lower Apicystis bombi prevalence in invaded sites (Appendix S5: Table S4). The growth-inhibiting effect of flavonoids has already been demonstrated for Plasmodium falciparum, belonging to the same phylum as A. bombi (i.e., Apicomplexa; Slavic et al 2009). Although the presence of secondary metabolites is a very strong hypothesis for explaining the lower prevalence of a subset of parasite species detected in Bombus pascuorum population from invaded sites, additional experimental assays (e.g., test on the biological activities of the secondary metabolites) are needed to fully validate this hypothesis and to understand the associated mechanisms.…”
Section: Parasite Prevalence and Impact Of Impatiens Glanduliferamentioning
confidence: 96%
“…This action of EGCG on GLUTs may be related to its gallate moiety, because ECG and genistein also have a blocking effect toward GLUTs, and ECG is the more potent 31, 39. The mechanism of EGCG to inhibit cellular glucose uptake may be either blockade of insulin signaling or direct competition with glucose for GLUTs 16, 43. We found that insulin-induced Ser473 phosphorylation of protein kinase B remained unchanged in the presence of EGCG in hepatocytes, adipocytes, myocytes, and beta cells 24 .…”
Section: Egcg Effect In Metabolic Tissuesmentioning
confidence: 99%